Analisis Kompleksitas Proses Bisnis Penerimaan Mahasiswa Baru Universitas Nahdlatul Ulama Blitar menggunakan Control-Flow Complexity dengan Pemodelan Business Process Modelling Notation - Fatmawati, Fariza Uma; Fauzan, Abd. Charis; Tricahyo, Vion Age (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The admission process for new students at universities requires efficient management, especially amidst the complexity brought by globalization. Universitas Nahdlatul Ulama Blitar faces challenges in the admission process. This study employs the Control-Flow Complexity metric and Business Process Modelling Notation to analyze the process. The results indicate an increase in complexity in the new version of student admission. The new version of student admission has a CFC measurement result of 13.5, compared to the old version of student admission which reached 6.5. These findings highlight the need for deeper understanding and identification of optimization points. The application of the CFC metric provides strong validation. This provides a basis for improving efficiency, transparency, and satisfaction for all parties involved in the new student admission process at Universitas Nahdlatul Ulama Blitar.